Solid aromatherapy material
By blending solid aromatherapy materials in the water-soluble phase and the non-water-soluble phase, the sustained release of aromatherapy in the aqueous environment is achieved, and the complex problem of aromatherapy sustained release module in the prior art is solved, and a simple and efficient aromatherapy sustained release solution is provided. Improves the service life and user experience of the product.
Patent Information
- Application Number
- CN202310778053.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing aromatherapy sustained release technology requires the design of a sustained release module separately in a water environment. It has a complex structure and is not simple and efficient enough, making it difficult to meet the aromatherapy needs of long-term use of products.
A solid aromatherapy material is provided, including a blended water-soluble and non-water-soluble phase, which slowly dissolves the aromatherapy material in water to realize the aromatherapy sustained release function without the need to design a self-injection device separately.
This solid aromatherapy material realizes simple and efficient sustained release of aromatherapy by adjusting the type and proportion of materials, improving the service life and user experience of the product.
Smart Images

Figure CN119220362A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aromatherapy, and in particular relates to a solid aromatherapy material. Background Art
[0002] Aromatherapy, as a new function of washing machine products, is recognized by more and more consumers. Relatively speaking, it is relatively simple to obtain the aromatherapy function, which can be achieved by adding plant essential oils, fragrances or fumigation. However, for products used for a long time, a slow-release aromatherapy function is usually required to meet the needs of consumers.
[0003] At present, the use scenarios of slow-release aromatherapy mainly include water environment and air environment. For water environment, such as washing machine, it is usually necessary to design a special slow-release module to automatically add liquid aromatherapy essential oil according to the program to achieve the slow-release function; the air environment is mainly to solidify the liquid essential oil into solid aromatherapy by adding specific ingredients, which evaporates slowly at room temperature or accelerates the volatilization at high temperature. At present, both of these aromatherapy schemes are used. However, for water environment, in order to achieve the slow-release function, it is usually necessary to design a slow-release module separately, which has high requirements on the structure and program of the washing machine, and the scheme is more complicated.
[0004] Based on these drawbacks, a simpler and more efficient aromatherapy sustained-release solution needs to be studied. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a solid aroma material. The water-soluble phase in the solid aroma material can be slowly dissolved in water, releasing the aroma material to produce fragrance; the solid aroma material is used in a washing device, and there is no need to design a separate self-dispensing device, and the aroma slow-release function can be simply and efficiently achieved.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a solid aromatherapy material, wherein the solid aromatherapy material comprises a blended water-soluble phase and a water-insoluble phase;
[0008] The water-soluble phase includes water-soluble polymer materials and aromatherapy materials;
[0009] The water-insoluble phase includes water-insoluble materials.
[0010] In some embodiments of the present invention, the water-soluble phase and the non-aqueous-soluble phase are both continuous phases.
[0011] In some embodiments of the present invention, the mass ratio of the water-soluble phase to the non-aqueous phase is (30-70):(30-70), preferably (40-60):(40-60).
[0012] In some embodiments of the present invention, the mass ratio of the water-soluble polymer material to the aromatherapy material is (70-90):(10-30).
[0013] In some embodiments of the present invention, the aromatherapy material is selected from one or more of chemical synthetics, natural plant essential oils and microcapsule essences.
[0014] In some embodiments of the present invention, the water-soluble polymer material is selected from one or more of polyvinyl alcohol, polyethylene glycol, polyethylene oxide, polyacrylamide and polyvinyl pyrrolidone.
[0015] In some embodiments of the present invention, the molecular weight of the water-soluble polymer material is 1 to 1 million.
[0016] In some embodiments of the present invention, the molecular weight of the polyvinyl alcohol is 800-5000.
[0017] In some embodiments of the present invention, the molecular weight of the polyethylene glycol is 100-4000.
[0018] In some embodiments of the present invention, the molecular weight of the polyethylene oxide is 50,000 to 1,000,000.
[0019] In some embodiments of the present invention, the water-insoluble material is a water-insoluble polymer material.
[0020] In some embodiments of the present invention, the water-insoluble polymer material is selected from one or more of polyolefins, polyesters and ethylene-vinyl acetate copolymers.
[0021] In some embodiments of the present invention, the molecular weight of the water-insoluble polymer material is 30,000 to 300,000.
[0022] In some embodiments of the present invention, the aromatherapy material comprises chemical synthetics and / or natural plant essential oils, the water-soluble polymer material is polyethylene oxide with a molecular weight of 100,000 to 1,000,000, the water-insoluble material is ethylene-vinyl acetate copolymer with a molecular weight of 30,000 to 100,000, and the mass ratio of the water-soluble phase to the water-insoluble phase is 50:50.
[0023] In some embodiments of the present invention, the aromatherapy material is microcapsule essence, the water-soluble polymer material is polyethylene oxide with a molecular weight of 100,000 to 1,000,000, the water-insoluble material is low-density polyethylene with a molecular weight of 30,000 to 100,000, and the mass ratio of the water-soluble phase to the water-insoluble phase is 50:50.
[0024] In some embodiments of the present invention, the tensile strength of the solid aromatherapy material is 5 MPa to 20 MPa, and the elongation at break is 5% to 600%.
[0025] In some embodiments of the present invention, the short side size of the phase region of the water-soluble phase is 100 nm to 10 μm; the short side size of the phase region of the non-water-soluble phase is 100 nm to 10 μm.
[0026] In some embodiments of the present invention, the dissolution rate of the solid aromatherapy material in water is 0.0001 g / L to 0.003 g / L.
[0027] In a second aspect, the present invention provides a solid aromatherapy material, wherein the solid aromatherapy material comprises a blended water-soluble phase and a water-insoluble phase;
[0028] The water-soluble phase contains aromatherapy materials;
[0029] The tensile strength of the solid aromatherapy material is 5MPa-20MPa, and the elongation at break is 5%-600%.
[0030] In some embodiments of the present invention, the short side size of the phase region of the water-soluble phase is 100 nm to 10 μm, and the short side size of the phase region of the water-insoluble phase is 100 nm to 10 μm.
[0031] In some embodiments of the present invention, the dissolution rate of the solid aromatherapy material in water is 0.0001 g / L to 0.003 g / L.
[0032] The dissolution rate test method is as follows: the solid aromatherapy material is prepared into a sample of 10 mm×10 mm×4 mm, with a mass of m1, and is rinsed with tap water at a flow rate of 2.5 L / min at room temperature. After the sample mass is constant, it is taken out and dried, and weighed, with a mass of m2. The volume of the water used for rinsing is v, and the dissolution rate = (m1-m2) / v;
[0033] The criterion for determining constant sample mass is: the mass difference before and after rinsing for 1 hour is less than 0.01 g;
[0034] All samples must be dried in a 60°C forced air drying oven before weighing, and the drying standard is that the mass difference before and after drying for 1 hour is less than 0.01g.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The solid aroma material provided by the present invention comprises a blended water-soluble phase and a non-water-soluble phase, wherein the water-soluble phase can be continuously and slowly dissolved in a water environment to release the aroma material to achieve a sustained-release effect. The phase region structure and sustained-release rate of the solid aroma material are controllable and can be adjusted by adjusting the type, molecular weight and proportion of the material. The solid aroma material is used in a washing device without the need to design a separate self-injection device, and the aroma sustained-release function can be simply and efficiently achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic diagram of the structure of a solid aromatherapy material provided by an embodiment of the present invention;
[0038] Figure 2 This is a SEM image of the non-water-soluble phase of the solid aromatherapy material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] In a first aspect, an embodiment of the present invention provides a solid aromatherapy material, wherein the solid aromatherapy material comprises a blended water-soluble phase and a non-water-soluble phase;
[0041] The water-soluble phase includes water-soluble polymer materials and aromatherapy materials;
[0042] The water-insoluble phase includes water-insoluble materials.
[0043] The solid aroma material provided by the present invention is prepared into a water-soluble phase material by adding the aroma material to a water-soluble material, and then the water-soluble phase material is blended with a non-water-soluble matrix. When the solid aroma material is in a water environment, the surface water-soluble phase material will dissolve with water to produce fragrance, and a porous structure will be formed on the matrix; the water flow further penetrates into the matrix along the pores, so that the water-soluble phase material in the inner layer of the matrix can also dissolve with water, thereby realizing the slow release of the aroma material in the water environment. When the solid aroma material is used in a washing device, there is no need to design a separate self-injection device, and the aroma slow release function can be simply and efficiently realized.
[0044] In some embodiments of the present invention, the water-soluble phase and the non-aqueous-soluble phase are both continuous phases.
[0045] In the present invention, the continuous phase refers to the water-soluble phase or the non-water-soluble phase in the solid aromatherapy material as a continuous whole, which is a continuous network structure in the solid aromatherapy material. When the water-soluble phase and the non-water-soluble phase are both continuous phases, a co-continuous structure is formed, which can ensure that the water-soluble phase can be completely dissolved with water, and on the other hand, the continuous non-water-soluble phase can provide a certain support effect to prevent the solid aromatherapy material from collapsing during the dissolution of the water-soluble phase.
[0046] In some embodiments of the present invention, the mass ratio of the water-soluble phase to the non-aqueous phase is (30-70):(30-70); for example, it can be 30:70, 32:68, 35:65, 38:62, 40:60, 42:58, 45:55, 48:52, 50:50, 52:48, 55:45, 58:42, 60:40, 62:38, 65:35, 68:32 or 70:30, etc. Preferably, it is (40-60):(40-60).
[0047] In some embodiments of the present invention, the mass ratio of the water-soluble polymer material to the aromatherapy material is (70-90):(10-30); for example, it can be 70:30, 72:28, 75:25, 78:22, 80:20, 82:18, 85:15, 88:12 or 90:10, etc.
[0048] In some embodiments of the present invention, the aromatherapy material is selected from one or more of chemical synthetics, natural plant essential oils and microcapsule essences.
[0049] Usually, chemical synthetic flavors and natural plant essential oils are mostly small molecule alcohols, aldehydes, derivatives, acids, amines, esters, terpenes, ethers, etc., such as dihydromyrcenol, cedarwood oil, citronellol, methyl ionone, ebyl alcohol, phytoncides, ethyl ionone, dihydrolyl ketone methyl ester, galaxol, lily of the valley aldehyde, methyl hexyl cinnamaldehyde. When these aromatherapy materials are processed at high temperature, some components may volatilize or react, causing the fragrance to change. Therefore, it is necessary to select appropriate carrier materials (such as water-soluble polymer materials and non-water-soluble materials that are conducive to low-temperature processing) and processing temperature according to their components.
[0050] Microcapsule flavors are aromatherapy materials that encapsulate flavors in microcapsule structures, which can significantly improve the heat resistance of the functional components of the flavors. The processing temperature mainly depends on the microcapsule shell structure. Therefore, for microcapsule flavors, carrier materials that are conducive to high-temperature processing and relatively higher processing temperatures (e.g., 120-170°C) can be selected.
[0051] In some embodiments of the present invention, the water-soluble polymer material is selected from one or more of polyvinyl alcohol, polyethylene glycol, polyethylene oxide, polyacrylamide and polyvinyl pyrrolidone.
[0052] In some embodiments of the present invention, the molecular weight of the water-soluble polymer material is 100 to 1 million; for example, it can be 100, 300, 500, 800, 1000, 2000, 3000, 5000, 6000, 8000, 10,000, 20,000, 30,000, 50,000, 80,000, 10,000, 120,000, 150,000, 180,000, 200,000, 220,000, 250,000, 280,000, 300,000, 320,000, 350,000, 380,000, 400,000, 420,000, 450,000, 480,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000 or 1 million, etc.
[0053] In some embodiments of the present invention, the molecular weight of the polyvinyl alcohol is 800-5000; for example, it can be 800, 900, 1000, 1200, 1500, 1800, 2000, 2200, 2500, 2800, 3000, 3200, 3500, 3800, 4000, 4200, 4500, 4800 or 5000, etc.
[0054] In some embodiments of the present invention, the molecular weight of the polyethylene glycol is 100-4000; for example, it can be 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1500, 2000, 2500, 3000, 3500 or 4000, etc.
[0055] In some embodiments of the present invention, the molecular weight of the polyethylene oxide is 50,000 to 1,000,000; for example, it can be 50,000, 80,000, 100,000, 120,000, 150,000, 180,000, 200,000, 220,000, 250,000, 280,000, 300,000, 320,000, 350,000, 380,000, 400,000, 420,000, 450,000, 480,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000 or 1,000,000, etc.
[0056] In some embodiments of the present invention, the water-insoluble material is a water-insoluble polymer material.
[0057] In some embodiments of the present invention, the water-insoluble polymer material is selected from one or more of polyolefins, polyesters and ethylene-vinyl acetate copolymers.
[0058] In some embodiments of the present invention, the molecular weight of the water-insoluble polymer material is 30,000 to 300,000; for example, it can be 30,000, 50,000, 80,000, 100,000, 120,000, 150,000, 180,000, 200,000, 220,000, 250,000, 280,000 or 300,000, etc.
[0059] In some embodiments of the present invention, the aromatherapy material comprises a chemical synthetic compound and / or a natural plant essential oil, the water-soluble polymer material is polyethylene oxide having a molecular weight of 100,000 to 1,000,000 (for example, 100,000, 120,000, 150,000, 180,000, 200,000, 220,000, 250,000, 280,000, 300,000, 320,000, 350,000, 380,000, 400,000, 420,000, 450,000, 480,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000 or 1,000,000, etc.), the water-insoluble material is an ethylene-vinyl acetate copolymer having a molecular weight of 30,000 to 100,000 (for example, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000 or 100,000, etc.), and the mass ratio of the water-soluble phase to the water-insoluble phase is 50:50.
[0060] In some embodiments of the present invention, the aromatherapy material is a microcapsule flavor, the water-soluble polymer material is a polyethylene oxide with a molecular weight of 100,000 to 1,000,000 (for example, 100,000, 120,000, 150,000, 180,000, 200,000, 220,000, 250,000, 280,000, 300,000, 320,000, 350,000, 380,000, 400,000, 420,000, 450,000, 480,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000 or 1,000,000, etc.), the non-water-soluble material is a low-density polyethylene with a molecular weight of 30,000 to 100,000 (for example, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000 or 100,000, etc.), and the mass ratio of the water-soluble phase to the non-water-soluble phase is 50:50.
[0061] In the present invention, the structure and sustained-release behavior of the solid aromatherapy material can be controlled by adjusting the type, molecular weight, and ratio of the water-soluble polymer material and the water-insoluble material. By controlling these factors within the above range of the present invention, it is helpful to form a co-continuous structure with the water-soluble phase and the water-insoluble phase, ensuring that the obtained solid aromatherapy material has a suitable sustained-release rate.
[0062] In some embodiments of the present invention, the tensile strength of the solid aromatherapy material is 5MPa to 20MPa, for example, 5MPa, 6MPa, 8MPa, 10MPa, 12MPa, 13MPa, 15MPa, 16MPa, 18MPa or 20MPa, etc.; the elongation at break is 5% to 600%, for example, 5%, 10%, 20%, 30%, 50%, 60%, 80%, 100%, 150%, 200%, 250%, 300%, 350%, 400%, 450%, 500%, 550% or 600%, etc. Compared with the existing solid aromatherapy formed by solidifying liquid essential oil, the solid aromatherapy provided by the present invention has higher tensile strength, the material can withstand greater tension during use, has higher durability and service life, which means longer service life and better user experience for aromatherapy.
[0063] In some embodiments of the present invention, the short side size of the phase region of the water-soluble phase is 100nm to 10μm, for example, it can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, etc.; the short side size of the phase region of the non-aqueous phase is 100nm~10μm, for example, it can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm.
[0064] It should be noted that the short side size of the phase region in the present invention refers to the minimum size of the phase region in different cross-sectional shapes in the direction passing through the center of the cross-sectional shape. For example, when the phase region at a certain location is cylindrical, the short side size of the phase region at that location is the diameter of the cylinder; when the phase region at a certain location is a thin sheet, the short side size of the phase region at that location is the thickness of the thin sheet.
[0065] In some embodiments of the present invention, the dissolution rate of the solid aromatherapy material in water is 0.0001 g / L to 0.003 g / L; for example, it can be 0.0001 g / L, 0.0002 g / L, 0.0003 g / L, 0.0004 g / L, 0.0005 g / L, 0.0006 g / L, 0.0007 g / L, 0.0008 g / L, 0.0009 g / L, 0.001 g / L, 0.0012 g / L, 0.0015 g / L, 0.0018 g / L, 0.002 g / L, 0.0022 g / L, 0.0025 g / L, 0.0028 g / L or 0.003 g / L, etc.
[0066] The dissolution rate test method is as follows: the solid aromatherapy material is prepared into a sample of 10 mm×10 mm×4 mm, with a mass of m1, and is rinsed with tap water at a flow rate of 2.5 L / min at room temperature. After the sample mass is constant, it is taken out and dried, and weighed, with a mass of m2. The volume of the water used for rinsing is v, and the dissolution rate = (m1-m2) / v;
[0067] The criterion for determining constant sample mass is: the mass difference before and after rinsing for 1 hour is less than 0.01 g;
[0068] All samples must be dried in a 60°C forced air drying oven before weighing, and the drying standard is that the mass difference before and after drying for 1 hour is less than 0.01g.
[0069] In the present invention, there is no particular limitation on the preparation method of the solid aromatherapy material. As an exemplary preparation method, it may include the following steps:
[0070] The water-soluble polymer material and the aromatherapy material are first blended to obtain a water-soluble phase material;
[0071] The water-soluble phase material and the water-insoluble phase material are subjected to a second blending to obtain the solid aromatherapy material.
[0072] Before the second blending, the water-soluble phase material may be granulated to obtain a water-soluble masterbatch; the particle size of the water-soluble masterbatch may be 2-5 mm.
[0073] The first blending and the second blending can be performed using a twin-screw extruder or an internal mixer.
[0074] When a twin-screw extruder is used, the processing temperature of the second blending can be 60-170°C (for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or 170°C, etc.), the screw speed of the second blending can be 50-150rpm (for example, it can be 50rpm, 60rpm, 70rpm, 80rpm, 90rpm, 100rpm, 110rpm, 120rpm, 130rpm, 140rpm or 150rpm, etc.), and the residence time can be 2-5min (for example, it can be 2min, 2.5min, 3min, 3.5min, 4min, 4.5min or 5min, etc.).
[0075] When an internal mixer is used, the mixing processing temperature of the second blending can be 80-170°C (for example, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or 170°C, etc.), the rotation speed can be 50-100rpm (for example, 50rpm, 60rpm, 70rpm, 80rpm, 90rpm or 100rpm, etc.), and the mixing time can be 5-10min (for example, 5min, 5.5min, 6min, 6.5min, 7min, 7.5min, 8min, 8.5min, 9min, 9.5min or 10min, etc.).
[0076] In the present invention, the blending method has a certain influence on the size and structure of the water-soluble phase and the non-water-soluble phase. By controlling the blending process conditions within the above range, it is helpful to form a co-continuous structure with a suitable phase domain size for the water-soluble phase and the non-water-soluble phase.
[0077] In a second aspect, an embodiment of the present invention provides a solid aromatherapy material, wherein the solid aromatherapy material comprises a blended water-soluble phase and a non-water-soluble phase;
[0078] The water-soluble phase contains aromatherapy materials;
[0079] The tensile strength of the solid aromatherapy material is 5MPa-20MPa, and the elongation at break is 5%-600%.
[0080] In some embodiments of the present invention, the short side size of the phase region of the water-soluble phase is 100 nm to 10 μm, and the short side size of the phase region of the water-insoluble phase is 100 nm to 10 μm.
[0081] In some embodiments of the present invention, the dissolution rate of the solid aromatherapy material in water is 0.0001 g / L to 0.003 g / L.
[0082] The technical solution of the present invention is further described below through specific implementation methods.
[0083] Example 1
[0084] This embodiment provides a solid aromatherapy material, and its structural schematic diagram is as follows Figure 1 As shown, the water-soluble phase ( Figure 1 The middle white area) and the non-aqueous phase ( Figure 1 middle black area);
[0085] Wherein, the water-soluble phase and the non-water-soluble phase are both continuous phases;
[0086] The water-soluble phase includes water-soluble polymer materials and aromatherapy materials, and the non-water-soluble phase includes non-water-soluble polymer materials;
[0087] The mass ratio of the water-soluble phase to the non-water-soluble phase is 50:50;
[0088] The mass ratio of the water-soluble polymer material to the aromatherapy material is 80:20;
[0089] The water-soluble polymer material is polyethylene oxide (Germany's Rhodamine Chemical Company, with a number average molecular weight of 100,000), the aromatherapy material is cedar oil, and the non-water-soluble polymer material is ethylene-vinyl acetate copolymer (UE630 from Taiwan Polymer Chemicals Co., Ltd., with a melt flow index of 1.5 g / 10 min).
[0090] The preparation method of the solid aromatherapy material in this embodiment is as follows:
[0091] (1) drying the polyethylene oxide at a drying temperature of 50° C. for a drying time of 6 h;
[0092] (2) using a twin-screw extruder, the polyethylene oxide and the cedar oil are first blended, the operating temperature of the twin-screw extruder is: the temperature of the first zone is 80° C., the temperature of the second zone is 100° C., the temperature of the third zone is 120° C., the temperature of the fourth zone is 120° C., the temperature of the fifth zone is 120° C., the temperature of the sixth zone is 120° C., and the die temperature is 110° C.; the screw speed is 50 rpm, and the material residence time is 3 min;
[0093] The mixture obtained by the first blending is air-cooled to below 50° C., and then granulated to obtain a water-soluble masterbatch with a particle size of 2-5 mm;
[0094] (3) using a twin-screw extruder, the water-soluble masterbatch obtained in step (2) is subjected to a second blending with ethylene-vinyl acetate copolymer, the operating temperature of the twin-screw extruder is: the temperature of zone 1 is 80° C., the temperature of zone 2 is 100° C., the temperature of zone 3 is 100° C., the temperature of zone 4 is 100° C., the temperature of zone 5 is 100° C., the temperature of zone 6 is 100° C., and the die temperature is 100° C.; the screw speed is 50 rpm, and the material residence time is 3 min;
[0095] The mixture obtained by the second blending is air-cooled to below 50° C., and then granulated to obtain a solid aromatherapy material.
[0096] Example 2
[0097] This embodiment provides a solid aromatherapy material, which is different from the embodiment 1 in that:
[0098] The mass ratio of the water-soluble phase to the non-water-soluble phase is 60:40;
[0099] The mass ratio of water-soluble polymer material to aromatherapy material is 70:30;
[0100] The water-soluble polymer material is polyvinyl alcohol (PVA-1799 from Anhui Wanwei Company, with a number average molecular weight of 1700), and the water-insoluble polymer material is ethylene-vinyl acetate copolymer (UE630 from Taiwan Polymer Chemicals Co., Ltd., with a melt flow index of 1.5 g / 10 min).
[0101] Example 3
[0102] This embodiment provides a solid aromatherapy material, which is different from the embodiment 1 in that:
[0103] The mass ratio of the water-soluble phase to the non-water-soluble phase is 40:60;
[0104] The mass ratio of water-soluble polymer material to aromatherapy material is 90:10;
[0105] The water-soluble polymer material is polyethylene glycol (polyethylene glycol-200 from Wuxi Yatai Chemical Industry Co., Ltd., with a number average molecular weight of 200), and the water-insoluble polymer material is ethylene-vinyl acetate copolymer (UE630 from Taiwan Polymer Chemicals Co., Ltd., with a melt flow index of 1.5 g / 10 min).
[0106] Example 4
[0107] This embodiment provides a solid aromatherapy material, and its structural schematic diagram is as follows Figure 1 As shown, the water-soluble phase ( Figure 1 The middle white area) and the non-aqueous phase ( Figure 1 middle black area);
[0108] Wherein, the water-soluble phase and the non-water-soluble phase are both continuous phases;
[0109] The water-soluble phase includes water-soluble polymer materials and aromatherapy materials, and the non-water-soluble phase includes non-water-soluble polymer materials;
[0110] The mass ratio of the water-soluble phase to the non-aqueous phase is 50:50;
[0111] The mass ratio of the water-soluble polymer material to the aromatherapy material is 80:20;
[0112] The water-soluble polymer material is polyethylene oxide (from Germany's Goodchem, with a number average molecular weight of 300,000), the aromatherapy material is microcapsule flavor ("lemon" flavor from Hefei Ruixue New Materials Technology Co., Ltd.), and the non-water-soluble polymer material is low-density polyethylene (low-density polyethylene 2426H from Maoming Petrochemical Company, with a number average molecular weight of 90,000).
[0113] The preparation method of the solid aromatherapy material in this embodiment is as follows:
[0114] (1) drying the polyethylene oxide at a drying temperature of 50° C. for a drying time of 6 h;
[0115] (2) Using a twin-screw extruder, the polyethylene oxide and the microcapsule flavor are first blended, the operating temperature of the twin-screw extruder is: the temperature of zone 1 is 80° C., the temperature of zone 2 is 120° C., the temperature of zone 3 is 140° C., the temperature of zone 4 is 140° C., the temperature of zone 5 is 140° C., the temperature of zone 6 is 140° C., and the die temperature is 120° C.; the screw speed is 50 rpm, and the material residence time is 3 min;
[0116] The mixture obtained by the first blending is air-cooled to below 50° C., and then granulated to obtain a water-soluble masterbatch with a particle size of 2-5 mm;
[0117] (3) using a twin-screw extruder, the water-soluble masterbatch obtained in step (2) is subjected to a second blending with low-density polyethylene, the operating temperature of the twin-screw extruder is: the temperature of zone 1 is 80° C., the temperature of zone 2 is 140° C., the temperature of zone 3 is 170° C., the temperature of zone 4 is 170° C., the temperature of zone 5 is 170° C., the temperature of zone 6 is 170° C., and the die temperature is 160° C.; the screw speed is 50 rpm, and the material residence time is 3 min;
[0118] The mixture obtained by the second blending is air-cooled to below 50° C., and then granulated to obtain a solid aromatherapy material.
[0119] Example 5
[0120] This embodiment provides a solid aromatherapy material, which is different from the embodiment 4 in that:
[0121] The mass ratio of the water-soluble phase to the non-water-soluble phase is 60:40;
[0122] The mass ratio of water-soluble polymer material to aromatherapy material is 70:30;
[0123] The water-soluble polymer material is polyvinyl alcohol (PVA-1799 from Anhui Wanwei Company, with a number average molecular weight of 1700), and the non-water-soluble polymer material is low-density polyethylene (low-density polyethylene 2426H from Maoming Petrochemical Company, with a number average molecular weight of 90,000).
[0124] Example 6
[0125] This embodiment provides a solid aromatherapy material, which is different from the embodiment 4 in that:
[0126] The mass ratio of the water-soluble phase to the non-water-soluble phase is 40:60;
[0127] The mass ratio of water-soluble polymer material to aromatherapy material is 90:10;
[0128] The water-soluble polymer material is polyethylene glycol (polyethylene glycol-200 from Wuxi Yatai Chemical Industry Co., Ltd., with a number average molecular weight of 200), and the non-water-soluble polymer material is low-density polyethylene (low-density polyethylene 2426H from Maoming Petrochemical Co., Ltd., with a number average molecular weight of 90,000).
[0129] Comparative Example 1
[0130] This comparative example provides a solid aromatherapy material, which is different from Example 1 only in that the mass ratio of the water-soluble phase to the water-insoluble phase is 20:80.
[0131] Comparative Example 2
[0132] This comparative example provides a solid aromatherapy material, which is different from Example 1 only in that the mass ratio of the water-soluble phase to the water-insoluble phase is 80:20.
[0133] Performance Testing:
[0134] The performance of the solid aromatherapy materials provided in the above embodiments and comparative examples were tested respectively, and the testing methods are as follows:
[0135] Tensile strength and elongation at break: The tensile properties were tested using a universal tensile testing machine. The test standard was GB / T1040-2006 and the tensile rate was 50 mm / min.
[0136] The test method of dissolution rate is as follows: the solid aromatherapy material is prepared into a sample of 10mm×10mm×4mm, with a mass of m1, and is rinsed with tap water at a flow rate of 2.5L / min at room temperature. After the mass of the sample is constant, it is taken out and dried, and weighed, with a mass of m2. The volume of the water used for rinsing is v, and the dissolution rate = (m1-m2) / v;
[0137] The criterion for determining constant sample mass is: the mass difference before and after rinsing for 1 hour is less than 0.01 g;
[0138] All samples must be dried in a 60°C forced air drying oven before weighing, and the drying standard is that the mass difference before and after drying for 1 hour is less than 0.01g.
[0139] Water-soluble phase continuity: prepare the solid aromatherapy material into a sample of 10mm×10mm×4mm, and weigh the mass m1; soak the sample in 30℃ water until the mass does not change, take out and dry, and weigh the mass m2; Water-soluble phase continuity = the mass of the water-soluble phase dissolved in the sample / theoretical mass of the water-soluble phase, the mass of the dissolved water-soluble phase = m1-m2.
[0140] Morphology characterization: Scanning electron microscopy (SEM) was used to observe the morphology of the solid aromatherapy material after soaking.
[0141] The results of the above tests are shown in Table 1 below:
[0142] Table 1
[0143]
[0144] From the test results in Table 1, it can be seen that the tensile strength of the solid aromatherapy material provided by the present invention is 5MPa-20MPa, the elongation at break is 5%-600%, the continuity of the water-soluble phase reaches 100%, and the dissolution rate in water is 0.0001g / L-0.003g / L.
[0145] The surface morphology of the solid aromatherapy material provided in Example 1 after soaking (non-water soluble phase) is as follows: Figure 2 As shown. Figure 2 It can be seen that the non-aqueous phase is continuous, and the short side dimensions of the phase regions of the non-aqueous phase and the aqueous phase (the void portion in the figure) are in the range of 100 nm to 10 μm.
[0146] Compared with Example 1, since the proportion of the water-soluble phase in Comparative Example 1 is relatively low, the water-soluble phase continuity of the obtained solid aromatherapy material is low, and a co-continuous structure cannot be formed, and the aromatherapy components are difficult to be completely released and the release speed is slow; since the proportion of the non-water-soluble phase in Comparative Example 2 is relatively low, the dissolution rate of the obtained solid aromatherapy material is too large, and the material is easy to disintegrate.
[0147] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A solid aromatherapy material, characterized in that: The solid aromatherapy material includes a blended water-soluble phase and a water-insoluble phase; The water-soluble phase includes water-soluble polymer materials and aromatherapy materials; The water-insoluble phase includes water-insoluble materials.
2. The solid aromatherapy material according to claim 1, characterized in that: The water-soluble phase and the non-aqueous phase are both continuous phases.
3. The solid aromatherapy material according to claim 1 or 2, characterized in that: The mass ratio of the water-soluble phase to the non-water-soluble phase is (30-70):(30-70), preferably (40-60):(40-60).
4. The solid aromatherapy material according to any one of claims 1 to 3, characterized in that: The mass ratio of the water-soluble polymer material to the aromatherapy material is (70-90):(10-30); Preferably, the aromatherapy material is selected from one or more of chemical synthetics, natural plant essential oils and microcapsule essences.
5. The solid aromatherapy material according to any one of claims 1 to 4, characterized in that: The water-soluble polymer material is selected from one or more of polyvinyl alcohol, polyethylene glycol, polyethylene oxide, polyacrylamide and polyvinyl pyrrolidone; Preferably, the molecular weight of the water-soluble polymer material is 1 to 1 million; Preferably, the molecular weight of the polyvinyl alcohol is 800 to 5000; Preferably, the molecular weight of the polyethylene glycol is 100 to 4000; Preferably, the molecular weight of the polyethylene oxide is 50,000 to 1,000,000.
6. The solid aromatherapy material according to any one of claims 1 to 5, characterized in that: The water-insoluble material is a water-insoluble polymer material; Preferably, the water-insoluble polymer material is selected from one or more of polyolefins, polyesters and ethylene-vinyl acetate copolymers; Preferably, the molecular weight of the water-insoluble polymer material is 30,000 to 300,000.
7. The solid aromatherapy material according to any one of claims 1 to 6, characterized in that: The aromatherapy material comprises chemical synthesis and / or natural plant essential oil, the water-soluble polymer material is polyethylene oxide with a molecular weight of 100,000 to 1,000,000, the water-insoluble material is ethylene-vinyl acetate copolymer with a molecular weight of 30,000 to 100,000, and the mass ratio of the water-soluble phase to the water-insoluble phase is 50:50; Alternatively, the aroma material is microcapsule essence, the water-soluble polymer material is polyethylene oxide with a molecular weight of 100,000 to 1,000,000, the water-insoluble material is low-density polyethylene with a molecular weight of 30,000 to 100,000, and the mass ratio of the water-soluble phase to the water-insoluble phase is 50:
50.
8. A solid aromatherapy material, characterized in that: The solid aromatherapy material includes a blended water-soluble phase and a water-insoluble phase; The water-soluble phase contains aromatherapy materials; The tensile strength of the solid aromatherapy material is 5MPa-20MPa, and the elongation at break is 5%-600%.
9. The solid aromatherapy material according to claim 8, characterized in that: The short side size of the phase region of the water-soluble phase is 100 nm to 10 μm, and the short side size of the phase region of the water-insoluble phase is 100 nm to 10 μm.
10. The solid aromatherapy material according to claim 8 or 9, characterized in that: The dissolution rate of the solid aromatherapy material in water is 0.0001 g / L to 0.003 g / L; The test method of the dissolution rate is as follows: the solid aromatherapy material is prepared into a sample of 10mm×10mm×4mm with a mass of m1, and is rinsed with tap water at a flow rate of 2.5L / min. After the mass of the sample is constant, it is taken out and dried, and weighed, with a mass of m2. The volume of the water used for rinsing is v, and the dissolution rate = (m1-m2) / v.
